2008
DOI: 10.1080/17477160801897208
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in morbidly obese adolescents: A 4-year follow-up of ten patients

Abstract: The laparascopic gastric banding operation was not as effective in weight reduction as expected. We have to turn our attention to compliance, postoperative treatment and the psychological component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…[19][20][21] The gastric bypass might be beneficial in adolescents with a risk of reduced compliance, as the weight loss is more consistent compared with after gastric banding. 11,22,23 The weight loss after gastric bypass has recently been demonstrated to be due to alterations in gastrointestinal and central neuroendocrine signaling causing reduced hunger, 24 augmented satiety, [25][26][27] possibly increased energy expenditure, 28 and altered taste perception and food preference. 29,30 A strong indication that physiological mechanisms determine weight loss after gastric bypass is that 93% of adolescents in our study achieved 450% excess weight loss despite a low number of outpatient visits, median 5 over 2 years compared with 20 visits in the O'Brien study.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The gastric bypass might be beneficial in adolescents with a risk of reduced compliance, as the weight loss is more consistent compared with after gastric banding. 11,22,23 The weight loss after gastric bypass has recently been demonstrated to be due to alterations in gastrointestinal and central neuroendocrine signaling causing reduced hunger, 24 augmented satiety, [25][26][27] possibly increased energy expenditure, 28 and altered taste perception and food preference. 29,30 A strong indication that physiological mechanisms determine weight loss after gastric bypass is that 93% of adolescents in our study achieved 450% excess weight loss despite a low number of outpatient visits, median 5 over 2 years compared with 20 visits in the O'Brien study.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive studies of adolescent bariatric surgery outcomes are in their infancy and are critically needed. Six published studies to date have reported on the psychosocial outcomes of adolescent bariatric surgery, including impressive weight outcomes of RYGBP (18,19) and laparoscopic‐adjustable gastric banding (20) in the United States as well as positive outcomes of laparoscopic‐adjustable gastric banding in Austria (21) and Israel (22). However, many of these studies were based on retrospective chart reviews and were limited by small sample sizes or nonsystematic and/or significant loss to follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have investigated psychosocial effects of bariatric surgery and the results are short term and based on small patient series’ [49]. Some studies indicate significant rates of high depression scores and negative self-acceptance in adolescents after laparoscopic adjustable gastric banding (LAGB) [50]. When bariatric surgery does not work as expected, people can feel shame and guilt [51], further enhancing the burden of being obese.…”
Section: Resultsmentioning
confidence: 99%